2020
DOI: 10.1002/sim.8477
|View full text |Cite
|
Sign up to set email alerts
|

Multikernel linear mixed model with adaptive lasso for complex phenotype prediction

Abstract: Linear mixed models (LMMs) and their extensions have been widely used for high‐dimensional genomic data analyses. While LMMs hold great promise for risk prediction research, the high dimensionality of the data and different effect sizes of genomic regions bring great analytical and computational challenges. In this work, we present a multikernel linear mixed model with adaptive lasso (KLMM‐AL) to predict phenotypes using high‐dimensional genomic data. We develop two algorithms for estimating parameters from ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 61 publications
0
22
0
Order By: Relevance
“…Converging evidence has shown that not all genetic variants and regions are predictive (Wen and Lu, 2020;Wen et al, 2016;Li, Lu and Wen, 2020;Speed and Balding, 2014;Weissbrod, Geiger and Rosset, 2016). Including noise can reduce the robustness and accuracy of the prediction model.…”
Section: Penalized Linear Mixed Model With Generalized Methods Of Moments Estimatorsmentioning
confidence: 99%
See 4 more Smart Citations
“…Converging evidence has shown that not all genetic variants and regions are predictive (Wen and Lu, 2020;Wen et al, 2016;Li, Lu and Wen, 2020;Speed and Balding, 2014;Weissbrod, Geiger and Rosset, 2016). Including noise can reduce the robustness and accuracy of the prediction model.…”
Section: Penalized Linear Mixed Model With Generalized Methods Of Moments Estimatorsmentioning
confidence: 99%
“…L 1 penalty is a commonly used technique for simultaneously selecting predictors and estimating their effect sizes. For example, Wen and Lu (2020) added an L 1 penalty to the log likelihood function of LMMs to simultaneously select predictive regions and estimate their effect sizes:…”
Section: Penalized Linear Mixed Model With Generalized Methods Of Moments Estimatorsmentioning
confidence: 99%
See 3 more Smart Citations